A RECONSTRUCTION OF THE CIVIL CODE ARTICLE BASED ON THE VALUE OF CONTRACTUAL JUSTICE - Hasyim, Dardiri (Lembaga Penelitian dan Pengabdian Masyarakat, 2020)
Justice contracts is essentially the fulfillment of rights and obligations in line with the principle of proportionality by observing the contract process from start to finish. The value of fairness in Contracting is: first, the principle of proportionality, where it governs the exchange of rights and obligations of the parties in accordance with proportion or part thereof; second, the principle of consensualism, in which it governs the agreement of both sides. The agreement is a conformity between the will and the statements made by the parties, so that legally an agreement can be held accountable; and third, the principle of freedom, in which it governs the freedom of a person in making a contract accompanied by good faith. Meanwhile, there are 9 (nine) chapters in the book III Civil Code of the partnership requiring the reconstruction of chapters.